2005
DOI: 10.1002/hyp.5867
|View full text |Cite
|
Sign up to set email alerts
|

The effect of land‐use changes on the hydrological behaviour of Histic Andosols in south Ecuador

Abstract: Abstract:The south Ecuadorian Andean mountain belt between 3500 and 4500 m altitude is covered by a highly endemic and fragile ecosystem called páramo. The Histic Andosols covering this region have highly developed hydric properties and exert a key function in the hydrological regulation of the páramo ecosystem. Unlike most Andosols, their extreme water retention capacity is not due to the presence of typical minerals such as allophane or imogolite. Although these minerals are virtually absent, the large organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 26 publications
5
135
0
6
Order By: Relevance
“…The mixture of poorly crystalline basaltic volcanic materials and peat, which dominates Icelandic wetland soils, is uncommon in the world, judging from our literature search. They differ from the paramo Histic Andosols of Ecuador (Buytaert et al 2005(Buytaert et al , 2007 and the Azores (Madeira et al 2007) in having a lower content of metal-humus complexes and a higher proportion of vitric materials deposited by continuous re-distribution of volcanic ash materials. The Icelandic wetland soils rarely exhibit hydric soil properties (>100 % water content at 15 bar tension) in contrast to more developed Hydric Andosols of warmer climates.…”
Section: The Inland Wetlands: Soils Vegetation and Birds Soilsmentioning
confidence: 87%
“…The mixture of poorly crystalline basaltic volcanic materials and peat, which dominates Icelandic wetland soils, is uncommon in the world, judging from our literature search. They differ from the paramo Histic Andosols of Ecuador (Buytaert et al 2005(Buytaert et al , 2007 and the Azores (Madeira et al 2007) in having a lower content of metal-humus complexes and a higher proportion of vitric materials deposited by continuous re-distribution of volcanic ash materials. The Icelandic wetland soils rarely exhibit hydric soil properties (>100 % water content at 15 bar tension) in contrast to more developed Hydric Andosols of warmer climates.…”
Section: The Inland Wetlands: Soils Vegetation and Birds Soilsmentioning
confidence: 87%
“…The geology of all catchments consists of Cretaceous and early Tertiary lavas and andesitic volcanoclastic deposits, shaped and compacted by glacier activity during the last ice age [Coltorti and Ollier, 2000;Hungerbühler et al, 2002]. The hydraulic conductivity of the bedrock is low, particularly compared to the hydraulic conductivity of the thin layer of volcanic ashes that constitute the soil layer [Buytaert et al, 2005]. On average, the soil layer is about 80 cm thick, with some bedrock outcroppings at convex locations and hilltops [Buytaert et al, 2006c].…”
Section: Experimental Catchmentsmentioning
confidence: 99%
“…[34] The absence of a dry season [Buytaert et al, 2006b], and the marked drop of soil hydraulic conductivity in nonsaturated conditions result in continuously wet soils (>60 vol% [Buytaert et al, 2005]). Field research has shown that also in dry periods a saturated soil layer exists above the bedrock, even on steep slopes [Buytaert et al, 2005].…”
Section: Hydrological Modelmentioning
confidence: 99%
“…This corresponds to a páramo, which is a tropical high-mountain ecosystem, characterised by soils with a high water storage capacity and high conductivity. The hydrologic behaviour of páramo is complex, and there are still major gaps in knowledge (Sevink, 2011;Reyes, 2014;Buytaert et al, 2005Buytaert et al, , 2006. Additionally, hydrometeorological data are scarce.…”
Section: Introductionmentioning
confidence: 99%